Predictability of Orographic Rainfall Features Over Sylhet Using Nwp Model (Journal of Engineering Science, 2020)
Topography and orography are two physical factors which produce high impact rainfall over the North-eastern part of Bangladesh. To predict the orographic rainfall of 29 March 2017 over Sylhet, Bangladesh an attempt has been performed using Weather Research and Forecasting (WRF) model. The model has been run in a single domain of 10 km horizontal resolution for 48-h and 72-h using six hourly global final datasets from 0000 UTC of each initial day of the event as initial and lateral boundary conditions with NSSL 2-moment microphysics scheme, Kain–Fritsch cumulous scheme and Yonsei University Planetary Boundary Layer (PBL) scheme. The model outputs such as sea level pressure, wind flow, vorticity, wind shear, humidity, Convective Available Potential Energy (CAPE), Convective Inhibition, Lifted Index, K-index, Total Total Index and rainfall have been analyzed. The model predicted weather parameters were visualized by Grid Analysis and Display System (GrADS) and Geographic Information System (GIS) software and validated with observed data of Bangladesh Meteorological Department (BMD), Tropical Rainfall Measuring Mission (TRMM) and European Centre for Medium-Range Weather Forecasts (ECMRWF) data. The analysis determines that the CAPE of magnitude 800- 1000 JKg-1, positive vorticity of (6-10) ×10-5s-1 and relative humidity of 80-100% up to 500-400 hPa levels are accountable for the happening of the orographic extreme rainfall and other parameters are compatible with the observed or theoretical values. This study indicates that the model with an appropriate model set up is capable to predict the orographic precipitation realistically well and can be used for upcoming events.Journal of Engineering Science 11(2), 2020, 61-73